Implementasi Karakter Pancasila melalui Tradisi Sambatan pada Masyarakat di Kabupaten Blitar - Cahyani, Arik; Kenlies Era Rosalina Marsudi (Antroposen: Journal of Social Studies and Humaniora, 2023)
Abstract: Indonesia is a country with Pancasila national character and has different traditions in each region. One is the splice or sambatan tradition that grows and develops in the community. This study aims to elaborate (1) the Paradigm of the Pancasila Character, (2) The Concept of the sambatan tradition in Society (3) The manifestation of the Pancasila character in the sambatan tradition. Researchers used a descriptive qualitative approach to collect data. Pancasila is the fundamental ideology used as the rationale for establishing and running the Indonesian state. As a Basic Ideology, Pancasila is used as a guideline for the character of life in culture, society, nation, and form. Indonesia has various traditions in different regions, one of which is in East Java. More precisely, in Blitar Regency, there is a tradition called sambatan with the definition of activities carried out in the community and solidarity among community members in working together to repair or build a house. Through various cultures in Indonesia, there is a tradition that contains values or rules for good moral behavior from the past to the present. This sambatan tradition focuses on social values that exist in society. This splice tradition is driven by a principle of reciprocity which means that those who have helped will receive help back from those who have been satisfied. Through this principle, services are exchanged in the context of helping to support. The Pancasila character embodied in Pancasila values is manifested through the “sambatan” tradition in the people of Blitar Regency